2015
DOI: 10.1038/jid.2015.166
|View full text |Cite
|
Sign up to set email alerts
|

Protein Tyrosine Kinase 6 Regulates UVB-Induced Signaling and Tumorigenesis in Mouse Skin

Abstract: Protein Tyrosine Kinase 6 (PTK6, also called BRK) is an intracellular tyrosine kinase expressed in the epithelial linings of the gastrointestinal tract and skin, where it is expressed in nondividing differentiated cells. We found PTK6 expression increases in the epidermis following UVB treatment. To evaluate the roles of PTK6 in the skin following UVB-induced damage, we exposed back skin of Ptk6 +/+ and Ptk6−/− SENCAR mice to incremental doses of UVB for thirty weeks. Wild type mice were more sensitive to UVB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 38 publications
2
10
1
Order By: Relevance
“…S1 A) and in most human colon tumors. In addition, manipulation of PTK6 expression did not have an impact on the activating tyrosine phosphorylation of two of its substrates, FAK (20) and BCAR1 (20) (data not shown), as previously demonstrated in human prostate cell lines (20), and in tumors that formed in mouse models of skin (16), and breast (29) cancer.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…S1 A) and in most human colon tumors. In addition, manipulation of PTK6 expression did not have an impact on the activating tyrosine phosphorylation of two of its substrates, FAK (20) and BCAR1 (20) (data not shown), as previously demonstrated in human prostate cell lines (20), and in tumors that formed in mouse models of skin (16), and breast (29) cancer.…”
Section: Discussionsupporting
confidence: 78%
“…Earlier we reported that PTK6 expression levels decrease in human squamous cell carcinomas of the skin (16). Comparison of PTK6 mRNA expression in several datasets (4350) suggests that PTK6 expression decreases in cancers that develop in tissues, which have appreciable levels of PTK6 in normal differentiated epithelial cells (Fig.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations